Potential Roles Of Methyltransferase Family 16 In Breast Cancer - Nur Aziz (Syntax Literate, 2022)
Three out of ten members of methyltransferase family 16 (Mtase16) have been separately demonstrated involves in cancer regulation. However, no study has been conducted to elucidate the potential roles of other Mtase16 family members in other types of cancer. This study aims to comprehensively identify the potential cancer regulator of Mtase16 family members in breast cancer adenocarcinoma (BRCA). To investigate the regulatory roles of Mtase16 family members in breast cancer, we employ bioinformatics analysis particularly by looking at the transcriptomic level of these methyltransferases in patients with breast cancer. The clinical relevancies of these methyltransferases were analyzed by survival analysis. Among Mtase16 family members, METTL18 showed upregulated in tumors compared to normal tissues in the TCGA-BRCA cohort. Lower survival probability is also being shown in breast cancer patients with high expression of METTL18. These results delineate METTL18 as a potential oncogene in breast cancer and further exploration of the mechanism study will hasten the therapeutic potential of targeting this protein in breast cancer.